Plasmonic Nanostructures for Energy Application - Pathak, Nilesh Kumar (Frontiers in Mechanical Engineering, 2020)
The present work furnishes the optical properties of metal nanostructures and their application in energy. Metal supports plasmonic resonances that can be tuned in the desired range of the solar spectrum by changing its size, shape, and surrounding environment. Two different systems, isolated and coupled gold metal nanospheres, are taken into account to study optical properties. These optical properties of the chosen nanostructure are analyzed in terms of surface plasmon resonances using the Boundary Element Method (BEM). The tuning of surface plasmon resonances under different parameter domains and their applications in energy are the main thrusts of this work. The simulated extinction spectrum and corresponding spectral width of metallic nanogeometries could be used in several applications like solar stills, solar collectors, and solar cells.